Effects of different nitrogen fertilizer types and rates on cotton leaf senescence, yield and soil inorganic nitrogen. Issue 11 (19th September 2021) - Yang, Xiuyi; Geng, Jibiao; Huo, Xianqi; Lei, Shutong; Lang, Ying; Li, Hui; Liu, Qianjin
ABSTRACT: The effects of different nitrogen fertilizer types and rates on cotton leaf photosynthesis, yield and soil inorganic nitrogen were studied in two years of field experiments. Seven treatments were carried out: (1) Polymer-coated urea (PCU) mixed with urea (1:1 ratio) applied once at 126 kg N ha −1 (70% BBF); (2) PCU mixed with urea (1:1 ratio) applied once at 180 kg N ha −1 (100% BBF); (3) urea applied once at 126 kg N ha −1 (70% U1); (4) urea applied once at 180 kg N ha −1 (100% U1); (5) urea applied twice at 126 kg N ha −1 (70% U2); (6) urea applied twice at 180 kg N ha −1 (100% U2); and (7) no nitrogen fertilizer (Control). The seed cotton yield of the mixed treatment increased by 6.27–17.69% on average per year compared with the U2 and U1 treatments at the same nitrogen rate. The net profit and nitrogen recovery efficiency increased by 15.53–46.68% and 4.37–16.32%, respectively. Leaf photosynthesis and soil inorganic nitrogen also increased. Compared with the 100% BBF treatment, the 70% BBF treatments, with 30% reduced N, had similar effects on cotton growth. These results provide a scientific basis for highly efficient fertilization during cotton cultivation.